2020
DOI: 10.1371/journal.pone.0228284
|View full text |Cite
|
Sign up to set email alerts
|

Associations between migraine occurrence and the effect of aura, age at onset, family history, and sex: A cross-sectional study

Abstract: IntroductionThe relationships between family history, sex, age at onset, and migraine occurrence have been documented. However, the associations between these factors across different sexes and subgroups of patients have yet to be elucidated. This study evaluated the association between family history and migraine in male and female patients experiencing episodic and chronic migraine with and without aura. MethodsThis cross-sectional, case-control study included 299 headache-free controls and 885 patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Migraine is hereditary, with many genetic variants, which, added to environmental factors, give it the denomination of a complex disorder [ 37 ]. Several studies have demonstrated the association of family history with migraine, finding differences according to sex [ 38 ] and age [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is hereditary, with many genetic variants, which, added to environmental factors, give it the denomination of a complex disorder [ 37 ]. Several studies have demonstrated the association of family history with migraine, finding differences according to sex [ 38 ] and age [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that a stronger family history of migraine is associated with a lower age-atonset, higher frequency and number of medication days, and the migraine with aura subtype (36). However, another study shows that family history was linked to an earlier age at onset, particularly in patients without aura (39). Moreover, in another study, the correlation between the early-onset group and a higher frequency of migraine attacks was not confirmed when adjusting for the years of illness (40).…”
Section: Early Onset Age Of Migrainementioning
confidence: 91%
“…An additional covariate to be incorporated is the age of migraine onset, as previous research has revealed that vestibular symptoms vary with the age of onset (30). Furthermore, family history is an important factor to consider in relation to age of onset, as previous studies have linked it to both sex and onset age (31), as well as the frequency of migraines (32) and vestibular symptoms (33). Therefore, this study will consider all these covariates.…”
Section: Covariatesmentioning
confidence: 99%